Efficacy of Selected Plant Extracts to Control Leaf Miner (Lyriomyza spp.) in Chrysanthemum - Rahardjo, Indijarto Budi; Marwoto, Budi; Budiarto, Kurniawan (AGRIVITA, Journal of Agricultural Science, 2020)
The use of eco-friendly methods in controlling pest and diseases has become an increasing concern in production system in many economically important crops, including ornamentals. The application of plant extract that has an insecticidal effect is considered as one promising alternative in reducing the negative effects of synthetic pesticides. The research was conducted to assess selected plant extracts in several concentrations against leaf miner (Lyriomyza spp.) in chrysanthemum. The experiment was carried out from January to December 2017 under plastic house conditions at the Indonesian Ornamental Crops Research Institute (IOCRI). The extracted organ of insecticidal plants regularly sprayed into chrysanthemum plants and compared with water as the controls. The results showed that the application of insecticidal plants extracts reduced attack intensity and incidence from water treatment (control). Certain treatment combinations, Chinese mahogany leaf extract at the concentration of 0.25%, C. pyrethrum petal 0.15 and 0.30%, and chinaberry leaf at 0.3, 0.35% even had 0.9-3.13% lesser attack incidences than commercial botanical insecticide Neem Plus. The respected treatments also supressed more than 62% leaf miner attacks and induced the increase of marketable flowers.